1972
DOI: 10.2466/pms.1972.34.2.623
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-Visual Differences in Human Temporal Judgment

Abstract: This paper reviews the research which demonstrated two intersensory differences in human time judgment: Sounds are judged longer than lights, and more information is transmitted via the judgment of auditory than visual durations. The intersensory difference in reaction time is also discussed and a theoretical schema with suggestions for future research is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
5
25
1
Order By: Relevance
“…A second feature of the present study was the inclusion of both auditory and visual timing signals within the same experimental session to better examine the effects of attention on duration classification. The observation that sounds are judged longer than visual stimuli of the same objective duration is a robust finding in the timing literature (e.g., Behar & Bevan, 1961;Goldstone et al, 1959;Goldstone & Lhamon, 1972, 1974Lustig & Meck, 2001;Penney et al, 1998Penney et al, , 2000Wearden et al, 1998) that has been interpreted to reflect greater attentional allocation to the auditory versus visual signal (Penney et al, 1998(Penney et al, , 2000. Thus, the inclusion of a dual modality bisection task permitted further investigation of the role of attention on temporal processing in schizophrenia, as impaired attention should produce a greater auditory/visual timing difference compared to that observed for nonpsychiatric participants.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…A second feature of the present study was the inclusion of both auditory and visual timing signals within the same experimental session to better examine the effects of attention on duration classification. The observation that sounds are judged longer than visual stimuli of the same objective duration is a robust finding in the timing literature (e.g., Behar & Bevan, 1961;Goldstone et al, 1959;Goldstone & Lhamon, 1972, 1974Lustig & Meck, 2001;Penney et al, 1998Penney et al, , 2000Wearden et al, 1998) that has been interpreted to reflect greater attentional allocation to the auditory versus visual signal (Penney et al, 1998(Penney et al, , 2000. Thus, the inclusion of a dual modality bisection task permitted further investigation of the role of attention on temporal processing in schizophrenia, as impaired attention should produce a greater auditory/visual timing difference compared to that observed for nonpsychiatric participants.…”
mentioning
confidence: 84%
“…In a previous study of mixed-modality temporal bisection, the offspring of individuals with schizophrenia exhibited an increased difference in their temporal judgments between auditory and visual signals compared with both controls and individuals identified as high-risk for the development of affective disorders . Based on these findings and reports of auditory/ visual differences observed using a variety of patient populations (Ehrensing et al, 1970;Goldstone & Kirkham, 1968;Goldstone & Lhamon, 1972;Lustig & Meck, 2001) and temporal discrimination tasks (Goldstone, 1968;Goldstone & Goldfarb, 1964;Goldstone et al, 1959), it was predicted that individuals with schizophrenia would judge the auditory stimuli as longer than visual stimuli of the same objective duration, and that this auditory/visual difference would be greater than that observed for the non-psychiatric participants. Because this is the first study to date to apply the SKE-MM model to bisection data from individuals diagnosed with schizophrenia, the model was applied as part of an exploratory analysis.…”
mentioning
confidence: 99%
“…Several studies in the literature have reported that auditory and audiovisual events are judged to be significantly longer than visual ones when duration estimates are observed in prospective situations (Goldstone & Goldfarb, 1964;Goldstone & Lhamon, 1972, 1974Walker & Scott, 1981;Wearden et al, 1998). Although it is unclear whether the overestimation bias for auditory events is relative to the events' actual durations or merely relative to the durations of visual events, it did not emerge here for either prospective or retrospective judgments.…”
Section: Discussionmentioning
confidence: 99%
“…The past literature has frequently reported that whereas visual (V) events are judged to be shorter than auditory (A) ones, auditory and audiovisual (AV) events produce comparable levels of performance (i.e., V Ͻ A ϭ AV; see, e.g., Goldstone & Lhamon, 1972, 1974Walker & Scott, 1981). To date, it is not clear why this bias occurs and whether it represents over-and underestimations, respectively, relative to events' actual durations, or simply two different magnitudes of over-or underestimation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation